Rainfall Trend Analysis in Context of Climate Change in Guercif City, Morocco - Hamdach, Youssef (European Scientific Journal, ESJ, 2019)
The purpose of this study is to analyze the variations of rainfall events through a statistical analysis of rainfall data in Guercif station for a period of 45 years (1971-2015). The analysis of rainfall trends in Guercif station showed that global warming which we are so concerned about seem to have resulted in an increase in rainfall and not drought. Moreover, the Gumbel method has allowed us to determine return periods of rainfall. The results have shown that the rainfall is low. The annual rainfall reaches a maximum of 359 mm with a 100 year return period.